ANALISIS UTANG LUAR NEGERI INDONESIA - Vivi Silvia; Sandy Tyas (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
The purpose of this study was to find out the factors that influence the external debt of Indonesia. To achieve the purpose, this study used independent variables which are exchange rate and gross domestic product (GDP). Data used in this study were secondary data sourced from a variety of reports and compilation, especially from Statistics Indonesia (BPS) and Bank Indonesia. Model used in this study was multiple linear regression with ordinary least squares method. The results of the calculations showed that the exchange rate and GDP positively and significantly affect the external debt of Indonesia. The coefficient of determination (Adj.R2=0.944) showed that 94.4% of external debt of Indonesia was affected by the exchange rate and GDP, while the rest or 5.6% was affected by other factors beyond this study, such as balance of payments deficit, government spending, the previous year government debt, export, and tax increase. The external debt really helped the Indonesian government to spur the economic growth rate in accordance with the predetermined targets. However, the external debt could cause various economic problems in Indonesia. In the era of economic crisis, the external debt of Indonesia was increased dramatically in the value of the rupiah that made the Indonesian government should ask for new external debt to pay the old external debt that has been matured.